Image of serpiginous choroiditis in swept-source optical coherence tomography angiography – a review of the literature - Kal, Magdalena; Płatkowska-Adamska, Bernadetta; Winiarczyk, Mateusz; Krupińska, Joanna; Mackiewicz, Jerzy; Odrobina, Dominik; Zarębska-Michaluk, Dorota (Klinika Oczna / Acta Ophthalmologica Polonica, 2023)
Serpiginous choroiditis (SC) is a bilateral, asymmetrical choroid inflammation leading to the loss of choriocapillaris, overlying retinal pigment epithelium (RPE), and outer retina causing the severe decrease of vision. This condition was initially diagnosed in patients with tuberculosis and syphilis, while autoimmune disorders are now considered to underlie this entity. Optical coherence tomography angiography (OCTA) is compa-rable to other invasive methods such as fluorescein angiography (FA) and indocyanine green angiography (ICGA) in diagnosing and monitoring the severity of the pathology mentioned above.